Water footprint concept, approaches, and applications: a comprehensive review for the agricultural sector - Demir, M. S.; Muratoglu, A. (2025)
Water footprint (WF) assessment has emerged as a vital tool for understanding and managing agricultural water consumption amid increasing water scarcity. This review synthesizes current knowledge and methodological developments in agricultural WF research, examining both volumetric and Life Cycle Assessment approaches. We analyze key methodological challenges, including water component differentiation, effective precipitation estimation, and calculation standardization across spatial scales. Recent trends show a shift from global assessments toward regional analyses, enabling precise water management strategies. The review evaluates WF reduction methods, demonstrating that optimized crop patterns and improved agricultural practices can significantly reduce water consumption. Integration of hydrological models with WF assessments shows promise for improving accuracy. Climate change, with varying regional impacts, emerges as a critical factor influencing future WF calculations. While WF methodology offers valuable insights for sustainable water management, its practical application requires careful consideration of regional contexts and limitations.